Morphological characterization of foamed natural filler-reinforced styrene maleic anhydride (SMA) composites - Gardner, Douglas J.; Aydemir, Deniz; Kızıltaş, Alper; Han, Yousoo; Gündüz, Gökhan; Aydemir, Deniz (Springer, 2014)
The aim of this study is to investigate the foaming of styrene maleic anhydride (SMA) matrix composites with a physical foaming agent, created during the reactive extrusion of natural fillers and SMA. The effect of lubricant on the foaming of SMA composites was also investigated. Whether particle’s crystallinity and hydroxyl number had any effect on cell size and cell density was also studied. The results showed that the greatest cell size and expansion occurred in the starch reinforced SMA composite which also exhibited the highest hydroxyl number and water by-product from reactive extrusion. Whereas microcrystalline cellulose-SMA composite exhibited the least cell number and expansion after extrusion because of the high crystallinity of MCC and the low hydroxyl number. Scanning electron microscopy results revealed that the cell distribution in foamed samples was heterogeneous and cell density increased from the core to skin layer. The results showed that hydroxyl number has an important effect on foaming and cell nucleation of the composites, and cell properties changed with filler’s percentage crystallinity.
Keywords: Reinforced composites; Hydroxyl number; Polymer composites; Foaming styrene maleic anhydride